2019
DOI: 10.4187/respcare.06998
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation During Cardiopulmonary Resuscitation: What Have We Learned From Models?

Abstract: The optimization of ventilation during cardiopulmonary resuscitation (CPR) is a broad field of research. Recent physiological observations in this field challenge the current understanding of respiratory and circulatory interactions. Thanks to different models available (bench, animal, human), the understanding of physiological phenomena occurring during CPR has progressed. In this review, we describe the clinical observations that have led to the emerging concept of lung volume reduction and associated thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 43 publications
(63 reference statements)
2
16
0
7
Order By: Relevance
“…When using PEEP, lower shunt fractions could be detected, particularly in early resuscitation, suggesting improved recruitment and optimized ventilation. This aligns with studies that showed that using PEEP during resuscitation can prevent airway closure and ensure alveolar ventilation (19,20) and has positive effects on systemic oxygenation (4,5,21). In our trial, oxygenation was improved when using PEEP, especially in early resuscitation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When using PEEP, lower shunt fractions could be detected, particularly in early resuscitation, suggesting improved recruitment and optimized ventilation. This aligns with studies that showed that using PEEP during resuscitation can prevent airway closure and ensure alveolar ventilation (19,20) and has positive effects on systemic oxygenation (4,5,21). In our trial, oxygenation was improved when using PEEP, especially in early resuscitation.…”
Section: Discussionsupporting
confidence: 86%
“…In our trial, oxygenation was improved when using PEEP, especially in early resuscitation. The ameliorated oxygenation could result from the prevention of atelectasis (4, 6, 7), thus decreasing shunt perfusion, improving lung recruitment and preventing airway closure (19,20). The EIT recordings showed normo-to hyperventilated lung areas when using PEEP, especially when ventilating with IPPV.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators speculate that intrathoracic airway closure eliminates the transmission of negative alveolar pressure generated during chest recoil. Thus, negative alveolar pressure is not facilitating airway opening and therefore does not generate any inspiratory flow despite a significant pressure gradient [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opening index, which was their bedside method of estimating airway patency of 20% to 70%, was still associated with low minute ventilation [ 14 ]. Thus, small amounts of PEEP (< 10 cmH 2 O) were able to maintain the airway patency, allowing the pressure gradient from the compression/recoil phases of CPR to reach the upper airway, improving effective alveolar ventilations caused by the compressions [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation